Evaluation Of Management, Treatment Outcomes And Health Related Quality Of Life Of Multidrug Resistant Tuberculosis Patients In Peshawar, Pakistan - Ahmad, Nafees (2016)
Globally, Pakistan is a multidrug resistant tuberculosis (MDR-TB) high burden country. Although, programmatic management of drug resistant TB (PMDT) in the country is initiated in 2010, but little is known about the management and treatment outcomes of MDR-TB patients from Pakistan. For this purpose, a total of 298 MDR-TB patients treated at the PMDT unit of Lady Reading Hospital Peshawar were included in an observational cohort study. Patients were followed until a treatment outcome was recorded. The majority of patients (55.8%) were resistant to second line anti-TB drugs (SLD), mainly a fluoroquinolone (52.7%). Patients with previous